Laqini - Isra Sabri (My University, 2023)
Communication is a desire that has been hard-wired in humans ever since. Its history can be traced back since the origin of speech circa. In fact, it was an effective survival mechanism for our ancestors, they shared information about food supplies, dangerous animals, and weather patterns. And up till Abstract Disclaimer this day, talking and sharing information make life easier. Even our values were passed on from conversations with our family, community, school and mosques. Meeting new individuals exposes you to a vast array of fresh perspectives, feelings, attitudes, and viewpoints. You might learn about stuff you had no idea existed. By offering you a fresh perspective, it might extend your horizons and give you a new sense of direction. You might choose to change your career. You can decide to research a novel and interesting topic or learn new things that a recent acquaintance showed you. The probabilities are endless! However, meeting new people is not that easy for all, this is where our application comes to help. We seek to build a mobile application that gives the chance to never miss the joy. The app will match you with others that are also free and curious to meet new people. After logging in the app and completing your profile, you could choose at any time to tell your surroundings that you’re looking to meet someone that also wants to do the same activity as you. You could also add a preferable gender, age range. If you both agreed to match, you could use the chatting feature to agree on the meeting details.